Analysis System of the Effect of Tax Rates on the Number of Goods Sent at the Post Office - Albertus Laurensius Setyabudhi (Engineering and Technology International Journal, 2022)
Application for changes to the minimum amount of Taxable Goods in PMK No. 19 the amount of tax owed. As a result, there is a decrease in interest in sending through the post office, this study was conducted to determine the extent of the impact of changes in tax rates on shipping so that it can be a reference for companies. Changes in tax rates affect the number of deliveries at the post office. and there is a very strong influence or 91.3% of the dependent variable can be influenced by the independent variable, while 8.7% is influenced by other variables not examined.